EPRO Diary: an App-based linkage to care model to promote compliance in pediatric liver transplant recipients in transition to adulthood. (March 2023) - Pasulo, L.; Leonardi, F.; Stroppa, P.; Casotti, V.; Merisio, A.; Spada, S.; D'Antiga, L.; Colledan, M.; Fagiuoli, S.
Abstract : Introduction: Adolescent liver transplant recipients represent a clinical challenge in the transition to adulthood. In particular, compliance remains the Achilles heel in this specific population. Low executive functions and quality of life markers were found to be similar to those observed in other chronic disease conditions of the childhhod. Methods: at our liver Transplant Center both adult and pediatric liver transplantations are performed (1024 adults and 677 pediatric LT from November 1997 to November 2022). Currently, 167 patients in the transition phase to adulthood, are being followed in our dedicated transitional outpatient clinic. In this setting, adolescents are evaluated jointly by pediatric- and adult- hepatologist with the concomitant support of the psychologist. A web base APPLICATION (downloadable on patient' own device) has been designed aiming to improve both the compliance and the relationship between transitioning adolescents and physicians. The APP allows the set-up of reminders for both drug intake and follow-up testings/exams, together with the recording of therapeutic schedule changes, blood tests results. A specific session dedicated to patients reported outcome with both psycologic and QoL testing) has been developed. The data entered in the app can be extracted online as chart output by both health care personnel and patients. Conclusion: ePRO Diary Liver has been built and approved within the ATRA(transitional outpatient clinic) project. The APP is currently available and patient enrollment is ongoing. This app can provide an updated support to young "native digital" liver transplant recipients during their transition to adulthood. This simple and intuitive application allows adolescent patients (and their caregivers, when needed) to insert reminders, appointments and blood tests in order to improve adherence to therapies and treatment plan. All data are shared with the transplant center, who can monitor the clinical situation in real time.